Wound healing properties of ethanolic extract of acrostichum aureum and acrostichum speciosum rhizome in rats - Herman, Hendy Putra; Darnis, Deny Susanti; Saad, Shahbudin; Bakhtiar, M. Taher; Ramli, Norazsida (Universiti Malaysia Kelantan Publisher, 2013)
This paper presents the assessment of wound healing properties of ethanolic extract of Acrostichum aureum and A. speciosum in rats. It was carried out on 6 treated groups with 6 rats each group. The excisional wound was made on the dorsal interscapular region of each rat by a 6 mm biopsy punch. T1 and T2 were treated with 5% and 10% A. aureum ethanolic extract in aqua cream, respectively. Meanwhile, T3 and T4 were treated with 5% and 10% A. speciosum ethanolic extract in aqua cream, respectively. Solcoseryl jelly and aqua cream were used as positive and negative controls. The treatments were applied topically twice daily, wound contraction and period of epithelization were measured every 2 days. The results showed that wound treated with 10% A. speciosum (T4) exerted faster wound contraction significantly (p < 0.05) compared to the negative control. It was also enhanced epithelization period (9.33 ± 3.20 days) of the wounds significantly (p < 0.05). In conclusion, these results strongly suggested the beneficial effects of both plant extracts for enhancing wound healing process.